TINGKAT PENGETAHUAN ORANG TUA TENTANG PENDIDIKAN SEKSUAL DINI PADA ANAK DI TK HARAPAN BANGSA BANJARMASIN - Feodora, Anisha Nanda; Nirmalasari, Nila; Husairi, Ahmad; Aflanie, Iwan; Panghiyangani, Roselina (Universitas Lambung Mangkurat, 2023)
Based on the results of interviews conducted with the parents of the seven students at Harapan Bangsa Kindergarten Banjarnasin, the four students already knew what sexual violence was, but had never provided education to their children because it was still considered taboo by children of their age. There are those who think that their children's education from school is sufficient, and there are also those who have provided education to their children about sexual violence. The purpose of this study is to know the level of knowledge of parents about awareness of the interests of early sexual education in children in Harapan Bangsa Banjarmasin Kindergarten. The research method used is observational, with data collection of parents of kindergarten students. The population used in this study was all parents of kindergarten students in Banjarmasin, The study sample was part of the population that was the subject of enelitian which was considered representative of the entire population using total sampling. The subjects of the study were all parents of 30 students of Harapan Bangsa Kindergarten in North Banjarmasin District who met the inclusion and exclusion criteria. The results showed that the level of parental knowledge of early sexual education in children in Harapan Bangsa Banjarmasin Kindergarten was 6 people (20%) good, 21 people (70%) were quite good, and 3 people (10%) were less.